2020
DOI: 10.3389/fpsyg.2020.612366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neurological Disorders on Bone Health

Abstract: Neurological diseases, particularly in the context of aging, have serious impacts on quality of life and can negatively affect bone health. The brain-bone axis is critically important for skeletal metabolism, sensory innervation, and endocrine cross-talk between these organs. This review discusses current evidence for the cellular and molecular mechanisms by which various neurological disease categories, including autoimmune, developmental, dementia-related, movement, neuromuscular, stroke, trauma, and psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 398 publications
(433 reference statements)
0
35
0
Order By: Relevance
“…; iv) psychotherapy for the treatment of the emotional components of the disease. Drug treatments for many ND, such as selective serotonin reuptake inhibitors, antipsychotics, anti-epilepsy drugs have independent and overlapping roles in mediating bone loss [5,16].…”
Section: Neurological Disorder Definition/etiology/prevalence Signals and Symptomsmentioning
confidence: 99%
See 3 more Smart Citations
“…; iv) psychotherapy for the treatment of the emotional components of the disease. Drug treatments for many ND, such as selective serotonin reuptake inhibitors, antipsychotics, anti-epilepsy drugs have independent and overlapping roles in mediating bone loss [5,16].…”
Section: Neurological Disorder Definition/etiology/prevalence Signals and Symptomsmentioning
confidence: 99%
“…Genetic, epigenetic, and various external factors, such as physical trauma, infection, and different aspects of the environmental surroundings can be involved with the initiation and the progression of the ND. Hormonal, immune, and molecular/cellular pathways impact the clinical presentation of the ND involving various systems [5]. Moreover, gut dysbiosis (microbiota dysregulation) has been associated with some neurodegenerative diseases [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of psychological factors in the etiology of chronic diseases is rousing the interest of the scientific community (Conversano, 2019 ; Martino et al, 2019b ; Merlo, 2019 ; Lenzo et al, 2020 ; Vicario et al, 2020 ), leading to an increase in research on neuropsychological correlates of a number of chronic illnesses including cardiovascular disease (Eikeseth et al, 2020 ), diabetes mellitus (Martino et al, 2019a ), bone health (Catalano et al, 2018 ; Fiegl et al, 2019 ; Kelly et al, 2019 , 2020 ; Lauriola et al, 2019 ; Williams et al, 2020 ), fibromyalgia (Veltri et al, 2012 ; Palagini et al, 2016 ; Conversano et al, 2019 ; Marchi et al, 2019 ), as well as neuropsychological problems such as attention and hyperactivity deficit (Fabio et al, 2018 ; Di Giuseppe et al, 2020c ) and post-traumatic stress disorder (Carmassi et al, 2014 , 2018 ; Settineri et al, 2018 ; Conversano et al, 2020a ; Merlo et al, 2020 ; Orrù et al, 2020 ). A number of recent studies have demonstrated that personality traits and implicit emotion regulation are associated with development, progression, recurrence, and severity of chronic illness (Koole and Rothermund, 2011 ; Ciuluvica et al, 2019 ; Settineri et al, 2019 ; Rymarczyk et al, 2020 ).…”
mentioning
confidence: 99%